Makna Ararem sebagai Pendampingan Pastoral dalam Perkawinan Etnik Biak di Propinsi Papua - Endemina Merry Apiem (Anthropos: Jurnal Antropologi Sosial dan Budaya (Journal of Social and Cultural Anthropology), 2021)
The purpose of writing this article is to analyze the meaning of ararem in the context of Biak ethnic marriage. In the Biak ethnic marriage tradition, there is a concept known as ararem. Ararem is a tradition of delivering the dowry of a future husband to his future wife. The provision of ararem has the following meanings, namely: first, the binding of kinship between clans / kerets, namely the male family and the female family, the second ararem as a sign of appreciation for women, third, the essential meaning of giving ararem as a sign of peace that contains prayer and The hope of a large family for a husband and wife to multiply to live happily and harmoniously in fostering a household. The research method uses descriptive analysis with a qualitative approach. This study will describe the sacredness of Ararem as assistance in Biak ethnic marriages and analyze Ararem as cultural heritage values which are used as counseling assistance in Biak ethnic marriages. In the tradition of ararem marriage, it is mandatory for Biak ethnicity to do so, because many ethnic groups believe that in ararem there is a sacred value, so if it is not done, then multi-ethnic marriage will not experience a happy and harmonious life. The purpose of writing this article is to understand the sacred value of ararem as a mentoring approach in pastoral by looking at local wisdom as a pattern of approach.